Evaluasi Kebijakan Pelayanan Website Sipraja Untuk Mewujudkan Good Governance - Mahmudah, Amanah Amalia (Saraq Opat: Jurnal Administrasi Publik, 2025)
In this era of rapid digital development, effective dan efficient public services require innovation in electronic-based service delivery. The Sidoarjo Regency Government has implemented an electronic-based government system by launching the Sidoarjo Public Service System (SIPRAJA) application and website. SIPRAJA aims to facilitate quick and easy independent management of population administration for the community. However, its implementation has faced challenges and has not fully met government expectations. This study evaluates the SIPRAJA website’s service policy in Banjarbendo Village, Sidoarjo District. Data was collected through interviews and documentation using a qualitative research method. The data analysis technique involved data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that SIPRAJA cannot be considered effective due to widespread user difficulties, frequent website slowdowns, and limited community participation. Efficiency indicators also show that SIPRAJA services are not yet efficient, hindered by operational hours, system design, and institusional and budgetary support. Adequacy is deemed unsuccessful due to limitations in data integration. However, equity has been achieved, as SIPRAJA has benefited all segments of society. Responsiveness indicators are also successful, reflecting the government’s swift response to citizen complaints. Furthermore, the accuracy indicator is considered successful, given the community’s familiarity with technological advancements.